Possible negative effects of snoring and increased sleep fragmentation on developmental status of preschool children. Issue 1 (7th January 2014) - Yorbik, Ozgur; Mutlu, Caner; Koc, Derya; Mutluer, Tuba
Abstract Limited studies have investigated the effects of snoring although harmful neurocognitive effects of obstructive sleep apnea syndrome are relatively well known. The aim of the present study was to investigate the effects of snoring and fragmented sleep on mental development in preschool children. The study population consisted of 212 healthy preschool children (age range 3.1–6 years; mean = 5.4 ± 0.6 years; 112 boys, 100 girls). The developmental status of the children was investigated by using the Ankara Developmental Screening Inventory (ADSI) and Peabody Picture Vocabulary Test (PBT). Children's sleep and snoring frequency were assessed by using parent completed Children's Sleep Habits Questionnaire (CSHQ). Snoring children had lower scores of language/cognitive skills, social/activities of daily living skills, and general development compared to controls (P < 0.05). The snoring group had more males, and more fragmented sleep than controls (P < 0.05). No significant difference was found in sleep duration between the snoring children and controls (P > 0.05). Children with fragmented sleep had lower scores of language/cognitive skills, fine motor skills, social/activities of daily living skills, and general development compared to controls (P < 0.05). In addition, no significant correlation was found between sleep duration and the developmental test scores (P > 0.05). Present study suggested that healthy preschool children who have habitual snoring or sleep fragmentation may have reduced scores of various mental development compared to controls. Uninterrupted sleep may be more important than sleep duration for the development of the various mental abilities in healthy preschool children. More studies investigating snoring and sleep fragmentation on mental development in children are warranted for a definite conclusion.